Changes in the expressions of the social issues of the homelessness - Tiengo, Verônica Martins (Pontifícia Universidade Católica de São Paulo, 2020)
This article discusses the formation of the homelessness, your linking to the capitalist mode of production and its changes, from commercial capitalism to neoliberal capitalism (developed in Brazil since the 1990). Rescue a few important elements like the "enclosure" (instrumental in the transition to capitalism). A distinction is made between the "beggars" of capitalism (who lived from begging only) of the current homelessness integrate working class and your survival depends on informal work.